Intellectual Capital under the View of Brazilian Enterprises Managers - Antunes, Maria Thereza Pompa (Review of Business Management, 2007)
This essay had the purpose to evaluate the interpretation of the top Brazilian companies’ managers towards the concept of Intellectual Capital, in comparison with the concept shown in the relevant literature, in order to raise data that could indicate the trends of the development and application of such concept within the Brazilian economic and business environment. The exploratory and descriptive research was based in a sample of 30 managers. The data analysis using qualitative method (cluster analysis and Mann-Whitney test) suggested that managers have an interpretation of the Intellectual Capital concept which is similar to the theory, and that they usually identify the elements in accordance with the theory and make investments on such elements. In addition to that, the research shows that managers have a tendency to utilize managerial control models due to the non-existence of follow-up on such investments. Therefore, according to the research, there is room for the development of models focusing the management of Intellectual Capital elements through This essay had the purpose to evaluate the interpretation of the top Brazilian companies’ managers towards the concept of Intellectual Capital, in comparison with the concept shown in the relevant literature, in order to raise data that could indicate the trends of the development and application of such concept within the Brazilian economic and business environment. The exploratory and descriptive research was based in a sample of 30 managers. The data analysis using qualitative method (cluster analysis and Mann-Whitney test) suggested that managers have an interpretation of the Intellectual Capital concept which is similar to the theory, and that they usually identify the elements in accordance with the theory and make investments on such elements. In addition to that, the research shows that managers have a tendency to utilize managerial control models due to the non-existence of follow-up on such investments. Therefore, according to the research, there is room for the development of models focusing the management of Intellectual Capital elements through Management Accounting. Key-words: Intellectual capital. Management accounting. Intellectual capital concept.